Novel disease-causing variants and phenotypic features of X-linked megalocornea - Dudakova, Lubica; Tuft, Stephen; Cheong, Sek-Shir; Skalicka, Pavlina; Jedlickova, Jana; Fichtl, Marek; Hlozanek, Martin; Filous, Ales; Vaneckova, Manuela; Vincent, Andrea L; Hardcastle, Alison J; Davidson, Alice E; et al. (Acta ophthalmologica, 2022)
PURPOSE: The aim of the study was to describe the phenotype and molecular genetic causes of X-linked megalocornea (MGC1). We recruited four British, one New Zealand, one Vietnamese and four Czech families. METHODS: All probands and three female carriers underwent ocular examination and Sanger sequencing of the CHRDL1 gene. Two of the probands also had magnetic resonance imaging (MRI) of the brain. RESULTS: We identified nine pathogenic or likely pathogenic and one variant of uncertain significance in CHRDL1, of which eight are novel. Three probands had ocular findings that have not previously been associated with MGC1, namely pigmentary glaucoma, unilateral posterior corneal vesicles, unilateral keratoconus and unilateral Fuchs heterochromic iridocyclitis. The corneal diameters of the three heterozygous carriers were normal, but two had abnormally thin corneas, and one of these was also diagnosed with unilateral keratoconus. Brain MRI identified arachnoid cysts in both probands, one also had a neuroepithelial cyst, while the second had a midsagittal neurodevelopmental abnormality (cavum septum pellucidum et vergae). CONCLUSION: The study expands the spectrum of pathogenic variants and the ocular and brain abnormalities that have been identified in individuals with MGC1. Reduced corneal thickness may represent a mild phenotypic feature in some heterozygous female carriers of CHRDL1 pathogenic variants.
Keywords: genetické nemoci vázané na chromozom X; megalocornea; Female; dědičné nemoci očí; keratokonus; Genetic Diseases, X-Linked; Humans; ženské pohlaví; Keratoconus; Phenotype; heterozygous carriers; lidé; Eye Diseases, Hereditary; posterior corneal vesicles; CHRDL1; fenotyp; keratoconus; brain MRI